A coupling simulation and optimization method developed for environmental-economic management of Lake watershed. (15th September 2022) - Zhang, Baichuan; Guo, Huaicheng; Zhang, Yang; Li, Zheng; Liu, Yanxiao; Wang, Shuhang; Fu, Zhenghui
Abstract: Many lake basins are facing the challenge of mitigating water shortage and water pollution while maintaining economic growth. Existing planning method for water pollution control often focus on how to alleviate water pollution effectively at the lowest cost, but rarely pay attention to the dynamic feedback and synergy effects between water pollution abatement, water conservation and social economy. This article proposes a method which consists of system dynamics model (SDM), Soil and Water Assessment Tool (SWAT) and objective programming model (OPM). It could be used to create insights on basin-wide water problems from a systematic perspective. The case study on Yilong Lake Watershed evaluates the proposed measures in existing local planning, calculates the optimal scheme, and discusses issues including the uncertainty of effectiveness, choice between recycling sewage and transferring outside, and the necessity of restricting food processing industry. This method could be improved on the simulation of social and industrial economy, the simulation of water cycle, and the spatial planning. Graphical abstract: Image 1 Highlights: System dynamics model and SWAT were coupled to simulate the environment-economic system. The conflict and synergy among social economy, water resources and aquatic environment were described. Limiting industry strictly is an inefficient way to improve sustainability for Yilong lake watershed. Recycling the wastewater and developing eco-friendly crop farming will help improve the sustainability of the watershed.